The high frequency of transformation procedure for expression of gus gene in chinaberry tree (Melia azedarach L.) using Agrobacterium - Thang, Bui Van; Dong, Do Xuan; Ha, Chu Hoang (Academia Journal of Biology, 2013)
An efficient transformation procedure for expression of gus gene was developed for Melia azadarach L. using hypocotyl explants. Hypocotyl explants from 12 day seedling precultured 2 days on induction media that containing 1.0 mg/l BAP, and 0.2 mg/l NAA. These samples were cocultured with Agrobacterium tumefaciens strain EHA101 harboring the binary vector pBI121 containing the gus and neomycin phosphotransferase II genes for 48 hours and transferred to selective regeneration media containing 0.5 mg/l BAP, 0.1 mg/l kinetin, 150 mg/l kanamycin, and 300 mg/l cefotaxime. After two passages on the selective regeneration media, the kanamycin-resistance shoots were transferred to the rooting media supplemented with 0.3 mg/l IBA, and 50 mg/l kanamycin. A strong β-glucuronidase activity was detected in the transformed plants by histochemical assay. Integration of T-DNA into the nuclear genome of transgenic plants was confirmed by polymerase chain reaction. This procedure geve effective transformation of Melia azadarach L. with 18.15% transformation frequency. The procedure proved to be stable and could be applied for transfering the useful genes into Melia azadarach L..